O ikonografii świętych w prawosławiu - Charkiewicz, Jarosław (Elpis, 2014)
The article consists of three paragraphs. The first one talks on roleof the veneration of icons in the Orthodox Church and concentrates onicons of the saints. Its main idea is that the icon, opposite to the portraitin Roman-Catholic Church, tries to show not the human face of thesaint but its spiritual, sanctified face of the saint. The second paragraph talks about iconographical canon and itsvarious elements, as: the role of the light in iconography, the face of thesaints that is presented on the icon, the body of the saints, the meaningthe different colors and various parts of the clothes, the attributes ofsaints, the importance of the time and the space in the icon, the place ofarchitecture and landscape in iconography as well as role and place of thewritings on the icons of the saints. The third, which is the main paragraph of the article, talks on the iconography of the different categories of the saints both the OldTestament as well as the New Testament. The author gives the short outline of the forming of the iconography of various types of saints aswell as explains the meaning of the parts of the clothes that saints wear.The categories of the saints that the author distinguish are as follows: theprophets, the ancestors (fathers, etc.), the apostles, the martyrs, equal-to-the-apostles, saint hierarchs of the Church, the venerable (the monastic),the right-believing, the witnesses, unmercenary physicians, the fools-for-Christ, the passion-bearers, the righteous (the just). The last, short paragraph gives the explanation of the place of the icons of the various saints in the iconostas.